GraphQL API test automation - Kolpakova, Alexandra; Buchalcevová, Alena, 1958-; Doležel, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
Master thesis work is specializing on problematics of implementation of GraphQL Application Programming Interface (API) test automation. The main goal is to compare existing GraphQL API test automation solutions to recommend one that can be used in a real project in a company that experienced a transition from Representational State Transfer (REST) to GraphQL API implementation and is searching for a new test automation approach.The first part of this paper focuses on explaining the important terms. The API role in client-server Web applications architecture style is defined with the HTTP characteristics that enables the communication between the client-side and the server-side. Further chapters give an overview on the REST architecture style and GraphQL technology for API implementation. The next part describes the API testing process, with its main testing activities and challenges.In the following parts of this thesis, the author introduces GraphQL API test automation solutions compatible with the Java programming language. These are then being compared, using the Multiple Criteria Decision Analysis, and the most beneficial solution is recommended to the concrete company that experienced the transition from REST to GraphQL API implementation.
Vedoucí práce: Alena Buchalcevová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses